Square over power of two sum

What is the value of i=1ni22i \sum_{ i=1 }^n \frac{i^2}{2^i} when n approaches infinity?

Note by Takeda Shigenori
7 years, 6 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Lemma 1: i=k12i=12k1\displaystyle\sum_{i=k}^\infty \dfrac{1}{2^i} = \dfrac{1}{2^{k-1}}. This is just geometric series.

Express i2=1+3+5++(2i1)i^2 = 1 + 3 + 5 + \ldots + (2i-1) and collect terms with equal numerators. We then have the sum to be:

(121+122+123+)+(322+323+)+(523+)+\left( \dfrac{1}{2^1} + \dfrac{1}{2^2} + \dfrac{1}{2^3} + \ldots \right) + \left( \dfrac{3}{2^2} + \dfrac{3}{2^3} + \ldots \right) + \left(\dfrac{5}{2^3} + \ldots \right) + \ldots

=j=1i=j2j12i= \displaystyle\sum_{j=1}^\infty \sum_{i=j}^\infty \dfrac{2j-1}{2^i}

=j=1(2j1)12j1= \displaystyle\sum_{j=1}^\infty (2j-1) \cdot \dfrac{1}{2^{j-1}} by Lemma 1.

Express 2j1=1+2+2++22j-1 = 1 + 2 + 2 + \ldots + 2 and collect terms with equal numerators, considering the 22s as distinct (so we collect the terms caused by the first 22, then caused by the second 22, and so on). The sum becomes:

(121+122+123+)+(222+223+)+(223+)+\left( \dfrac{1}{2^1} + \dfrac{1}{2^2} + \dfrac{1}{2^3} + \ldots \right) + \left( \dfrac{2}{2^2} + \dfrac{2}{2^3} + \ldots \right) + \left(\dfrac{2}{2^3} + \ldots \right) + \ldots

=j=012j+j=1i=j22i= \displaystyle\sum_{j=0}^\infty \dfrac{1}{2^j} + \sum_{j=1}^\infty \sum_{i=j}^\infty \dfrac{2}{2^i}

=121+j=1212j1= \dfrac{1}{2^{-1}} + \displaystyle\sum_{j=1}^\infty 2 \cdot \dfrac{1}{2^{j-1}} by Lemma 1.

=2+2121=6= 2 + 2 \cdot \dfrac{1}{2^{-1}} = \boxed{6}


Another solution:

Lemma 1: (1+x+x2+x3+)3=i=0(i+22)xi(1+x+x^2+x^3+\ldots)^3 = \sum_{i=0}^\infty \binom{i+2}{2} x^i. This is from the generating function solution of solving a+b+c=ia+b+c=i where a,b,ca,b,c are nonnegative integers.

Thus,

(1+x+x2+x3+)3x(1+x+x^2+x^3+\ldots)^3x

=i=0(i+22)xi+1= \displaystyle\sum_{i=0}^\infty \binom{i+2}{2} x^{i+1}

=i=1(i+12)xi= \displaystyle\sum_{i=1}^\infty \binom{i+1}{2} x^i

=i=1i(i+1)2xi= \displaystyle\sum_{i=1}^\infty \dfrac{i(i+1)}{2} x^i

and

(1+x+x2+x3+)3x2(1+x+x^2+x^3+\ldots)^3x^2

=i=1i(i+1)2xi+1= \displaystyle\sum_{i=1}^\infty \dfrac{i(i+1)}{2} x^{i+1} from previous result

=i=2(i1)i2xi= \displaystyle\sum_{i=2}^\infty \dfrac{(i-1)i}{2} x^i

=i=1i(i1)2xi= \displaystyle\sum_{i=1}^\infty \dfrac{i(i-1)}{2} x^i because at i=1i=1 the term gives 00

So we have

(1+x+x2+x3+)3(x2+x)(1+x+x^2+x^3+\ldots)^3(x^2+x)

=i=1(i(i1)2+i(i+1)2)xi= \displaystyle\sum_{i=1}^\infty \left( \dfrac{i(i-1)}{2} + \dfrac{i(i+1)}{2} \right) x^i

=i=1i2xi= \displaystyle\sum_{i=1}^\infty i^2 x^i

Substituting x=12x = \dfrac{1}{2}, the right hand side gives the expression we need, while the left hand side can now be easily evaluated to 23(14+12)=62^3 \cdot \left( \frac{1}{4} + \frac{1}{2} \right) = \boxed{6}.

Ivan Koswara - 7 years, 6 months ago

Let

S=i=1i22iS=\sum_{i=1}^\infty\frac{i^2}{2^i}

We have

2S=i=1i22i+1=i=0(i+1)22i=1+i=1(i+1)22i\begin{aligned} 2S&=\sum_{i=1}^\infty\frac{i^2}{2^{i+1}}\\&=\sum_{i=0}^\infty\frac{(i+1)^2}{2^i}\\&=1+\sum_{i=1}^\infty\frac{(i+1)^2}{2^i} \end{aligned}

Subtracting the two, we get

2SS=S=1+i=1(i+1)2i22i=1+i=12i+12i=1+i=12i2i+i=112i=2+2i=1i2i\begin{aligned} 2S-S&=S\\&=1+\sum_{i=1}^\infty\frac{(i+1)^2-i^2}{2^i}\\&=1+\sum_{i=1}^\infty\frac{2i+1}{2^i}\\&=1+\sum_{i=1}^\infty\frac{2i}{2^i}+\sum_{i=1}^\infty\frac{1}{2^i}\\&=2+2\sum_{i=1}^\infty\frac{i}{2^i} \end{aligned}

Now, this is an arithmetico-geometric series. Hence, its sum is

S=2+12112+121(112)2=6S=2+\frac{\frac{1}{2}}{1-\frac{1}{2}}+\frac{\frac{1}{2}\cdot1}{\left(1-\frac{1}{2}\right)^2}=\boxed{6}

Now instead, let's pretend that this is the day of the test and you forgot the formula for a arithmetico-geometric series. What would you do? Well, it appears as though our manipulation turned the numerator from i2i^2 to ii. Hm. Maybe if we manipulate it more, we can turn that ii to a 11 and then solve using geometric series! Let's see:

S=i=1i2iS'=\sum_{i=1}^\infty\frac{i}{2^i} 2S=i=1i2i+1=i=0i+12i=1+i=1i+12i\begin{aligned} 2S'&=\sum_{i=1}^\infty\frac{i}{2^{i+1}}\\&=\sum_{i=0}^\infty\frac{i+1}{2^i}\\&=1+\sum_{i=1}^\infty\frac{i+1}{2^i} \end{aligned} 2SS=S=1+i=112i2S'-S'=S'=1+\sum_{i=1}^\infty\frac{1}{2^i}

Hooray! It worked! So S=1+1=2S'=1+1=2 from geometric series, hence S=2+2S=2+2(2)=6S=2+2S'=2+2(2)=\boxed{6}, again.

Cody Johnson - 7 years, 6 months ago
×

Problem Loading...

Note Loading...

Set Loading...